2015
DOI: 10.5901/ajis.2015.v4n2p11
|View full text |Cite
|
Sign up to set email alerts
|

Public Private Participation for Infrastructure in Developing Countries

Abstract: Of recent, significant development in the use of public private partnership in providing infrastructural facilities has become a new policy initiative in many countries, Nigeria inclusive. This became necessary in view of the inadequacy of existing infrastructures to cope with the demands of the urban dwellers due to the inability of the government at various levels to provide and maintain urban infrastructures which are essential ingredients of economic development of the nation. Apart from the acute shortage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Moreover, the public should be educated and made aware of the involvement of the private sector in planning and financing public infrastructure projects (Adeyinka and Olugbamila, 2015). Ogunsemi et al (2006) add that programmes to enlighten the communities and the country at large are needed.…”
Section: Jfmpc 243mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the public should be educated and made aware of the involvement of the private sector in planning and financing public infrastructure projects (Adeyinka and Olugbamila, 2015). Ogunsemi et al (2006) add that programmes to enlighten the communities and the country at large are needed.…”
Section: Jfmpc 243mentioning
confidence: 99%
“…Conducive environment for investment Any private investments directed to infrastructure development, political will and commitment to partner with available financiers are required (Adeyinka and Olugbamila, 2015;KPMG, 2015). An investmentfriendly environment is of the utmost importance to attract and involve private participation.…”
Section: Jfmpc 243mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, the government adjusted certain policies to open up opportunities for private partnership (Udoka 2013). Moreover, Adeyinka and Omotayo (2015) observed that this has not been fully implemented, as only about 15% accrues due to public private partnership. Although the Nigerian government recognizes the importance of infrastructure investment and has shown increasing interest in demonstrating a higher political commitment to invest, particularly in the agricultural sector, Daze et al (2011) observed that, in reality, the details of plans are quite different from those presented in policy documents.…”
Section: Agricultural Infrastructure Policies and Management In Nigeriamentioning
confidence: 99%
“…The origins of the public-private partnership as an institutionalized tool can be traced in United Kingdom, where, after the utilization of tollgates authorized in the fourteenth century and the first urnpike model in the seventeenth century (Grimsey and Lewis, 2004), "Private Finance Initiative" tool has been set up (Corner, 2005;Adeyinka and Olugbamila, 2015). Several forms of cooperation between the public and the private subjects -project financing, public company, service contracts, operation and management contracts, leasing-type contracts, build-operate-transfer (BOT), design-build-finance-operate (DBFO)have been subsequently developed.…”
Section: Introductionmentioning
confidence: 99%